Improving students’ responsibility in tennis courses: “The Silent Movement” model for physical education programme - Kesumawati, Selvi Atesya; Makorohim, M. Fransazeli; Fikri, Aprizal; Fahritsani, Husni (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2024)
Background: Tennis courses are a mandatory component prepared for prospective physical education teachers in universities. However, many students do not achieve optimal learning outcomes due to the irresponsible attitude of students, which can hinder the learning process. Research Objective: The purpose of this study is to develop and produce a tennis learning model (Silent Movement Tennis) for increasing the sense of personal and social responsibility in students. Silent Movement Tennis is the latest model in tennis learning, and there has been no previous research. Method: This research used the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) method in producing a learning model called “Silent Movement Tennis,” which consists of 4 movement skill activity posts that must be carried out by every student with a sense of responsibility. The respondents of this study are all 4th semester students (academic year 2023-2024), totalling 30 people, consisting of 9 females and 21 males at a university in the city of Palembang. The Silent Movement Tennis model was also validated by 3 experts consisting of 1 learning planning expert, 1 tennis practitioner, and 1 developmental psychologist and analysed using the Content Validity Index (CVI) and Content Validity Ratio (CVR). Finding/Result: The results of validation by experts who have been analysed show the value of the Content Validity Index (CVI) shows an average score of 3.63, and the Content Validity Ratio (CVR) analysis shows an average score of 0.27, which means the model developed is appropriate, relevant, or good, and also high content validity to increase the sense of social and personal responsibility for students. Conclusion: Silent Movement Tennis model as an alternative model to improve basic tennis skills and student responsibility. Future research efforts must focus on the design and implementation of sports values programs, namely by developing learning games and other sports based on the TPSR model to foster and develop a sense of personal and social responsibility that is important for students to become an adaptive and resilient generation, which ultimately contributes to their future success.